2009
DOI: 10.1186/1475-2891-8-50
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effectiveness of class-based nutrition intervention on changes in soft drink and milk consumption among young adults

Abstract: Background: During last few decades, soft drink consumption has steadily increased while milk intake has decreased. Excess consumption of soft drinks and low milk intake may pose risks of several diseases such as dental caries, obesity, and osteoporosis. Although beverage consumption habits form during young adulthood, which has a strong impact on beverage choices in later life, nutrition education programs on beverages are scarce in this population. The purpose of this investigation was 1) to assess soft drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…At the beginning of the study, only 13% of total study participants ate more than one serving of fruit per day, though the average consumption of fruit (0.4) was similar or less than previous studies [20,27]. After the coursework this number increased up to 26%.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…At the beginning of the study, only 13% of total study participants ate more than one serving of fruit per day, though the average consumption of fruit (0.4) was similar or less than previous studies [20,27]. After the coursework this number increased up to 26%.…”
Section: Discussionmentioning
confidence: 58%
“…However, overall, study participants did not meet the recommended intake of most type of food in this study. The effectiveness of nutrition education in weight management, food choice and nutritional behavior was well addressed in a wide range of literature [27-29]. For example, school based nutrition education decreased soft drink consumption but increased milk and dairy products in female and male college students [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bergen and Yeh (2006) found that vending machines with clear labels for beverages that contain no energy (i.e., “0 calories, 0 carbs”) and motivational posters encouraging the consumption of non-energy beverages had a lower growth rate of SSB sales compared to control machines with no labels or posters. In another intervention, Ha, Caine-Bish, Holloman, and Lowry-Gordon (2009) found a reduction in SSB consumption among college students who took a basic nutrition class. Finally, in a behavioral-economics approach, Yang and Chiou (2010) found that when college students were provided money to buy a beverage of their choice they often bought the lower-priced beverage unless they had been exposed to health-concerns information; in that case, they bought the healthy alternative—even when its price was higher.…”
mentioning
confidence: 98%
“…An emphasis on outcome expectations and expectancies along with adolescents' attention points when designing nutrition promotion programs may drive adolescents to increase F&V consumption. Several previous studies have conducted nutrition education programs focusing on health effects 18 or chronic disease prevention [19][20][21] to improve healthy food consumption among college students or young adults. Positive changes in eating habits have been found in some food groups.…”
Section: Introductionmentioning
confidence: 99%